1963
DOI: 10.1063/1.1733960
|View full text |Cite
|
Sign up to set email alerts
|

On the Infrared Spectrum of Hydrogen Peroxide Matrix-Isolation Studies of the System H2O2:N2 (II)

Abstract: Matrix-isolation spectra of the system H2O2:N2 were obtained in the region 4000–300 cm—1 at 4.2°K. Spectra taken in this manner are free of complications due to association, over-all rotation, etc. The most unusual feature of these spectra is the band system at 385 and 350 cm—1 in the torsional region. This main band at 385 cm—1 is exceedingly broad for a matrix spectrum. These bands have been assigned to the n=0→1 and 1→2 torsional transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…This peak was attributed to y 6 , the asymmetric bending mode and is in agreement with the previous observations by Catalano and Sanborn, who investigated the infrared spectrum of hydrogen peroxide in nitrogen. 10 This work therefore reiterates the findings of Catalano and Sanborn in that a significant shift was observed away from the gas-phase band centre at 1266 cm À1 . 11 The water vapour in the system as a consequence of bubbling through a solution of aqueous hydrogen peroxide was clearly observed in the spectra in the region between 1350 and 2000 cm À1 .…”
Section: Resultssupporting
confidence: 88%
“…This peak was attributed to y 6 , the asymmetric bending mode and is in agreement with the previous observations by Catalano and Sanborn, who investigated the infrared spectrum of hydrogen peroxide in nitrogen. 10 This work therefore reiterates the findings of Catalano and Sanborn in that a significant shift was observed away from the gas-phase band centre at 1266 cm À1 . 11 The water vapour in the system as a consequence of bubbling through a solution of aqueous hydrogen peroxide was clearly observed in the spectra in the region between 1350 and 2000 cm À1 .…”
Section: Resultssupporting
confidence: 88%
“…In addition to this, the band at 1292 cm -1 in ZnO-treated GZ3 strongly suggests the presence of O-H asymmetric bending in H 2 O 2 which is absent in pure glucose and bare GZ3. It confirms the oxidation of glucose to form the gluconic acid and H 2 O 2 [42,45]. As a result, the oxidation reaction provides two electrons as discussed in the above equation and these electrons can transfer to the ZnO:rgo composite as it is an efficient electron acceptor which enhances the electronhole pair recombination resulting in the enhancement of the band emission at 574 nm.…”
Section: Glucose Sensingsupporting
confidence: 56%
“…Multiple infrared studies have shown the presence of both bulk and monomer features. [20][21][22][23]25,27 For H 2 O 2 the bulk and monomer contributions are separated (3572 and 3581 cm À1 vs. 1370 cm À1 , respectively). The OH-stretch monomer features of H 2 O at 3724 and 3732 cm À1 are not observed and we therefore conclude that water is not abundantly formed in O 2 -rich environments.…”
Section: Discussionmentioning
confidence: 99%